Development of Augmented Reality Application for Exercise to Promote Health among Elderly - Paweena Bangkerd; Thosporn Sangsawang (Indonesian Journal of Educational Research and Technology, 2021)
This research aimed to: (1) develop and find the effectiveness of augmented reality application for exercise to promote health among elderly, (2) compare physical fitness in terms of flexibility of the elderly before and after exercising by augmented reality application for exercise to promote health among elderly, and (3) study elderly satisfaction towards the use of augmented reality application for exercise. The samples were 30 elderly in Bueng Namrak, Thailand. The samples were selected through a purposive sampling technique. The instruments were augmented reality application for exercise to promote health among elderly, physical fitness test in terms of flexibility, and satisfaction form. The results showed that learning and using augmented reality application for exercise to promote health among elderly was effective according to KW1 80.80 at KW1 80/83.33. The physical fitness in terms of flexibility after using the application was higher than before using the application. The physical fitness in terms of flexibility before using the application was 5.91 in average, with standard deviation of 6.76, whereas the average after using the application was 6.15, with the standard deviation of 6.53. The t-test value after using the application was 2.80 at a statistically significant level of.05. The satisfaction of the elderly towards the use of augmented reality application for exercise to promote health among elderly was 4.64 in average, which was at the highest level.